Monarch Butterfly, Danaus plexippus Linnaeus (Lepidoptera: Nymphalidae: Danainae) - Andrei Sourakov (EDIS)
EENY-442, a 9-page illustrated fact sheet by Andrei Sourakov, is part of the Featured Creatures collection. It describes this well-known migrating butterfly with charismatic appearance, their distribution, description, biology and life cycle, hosts and monarch toxicity, conservation status, and natural enemies. Includes references. Published by the UF Department of Entomology and Nematology, November 2008.